Fully Solution‐Processed Semi‐Transparent Perovskite Solar Cells With Ink‐Jet Printed Silver Nanowires Top Electrode. Issue 2 (10th January 2018) - Xie, Menglan; Lu, Hui; Zhang, Lianping; Wang, Jie; Luo, Qun; Lin, Jian; Ba, Lixiang; Liu, Hong; Shen, Wenzhong; Shi, Liyi; Ma, Chang‐Qi
Abstract : Owing to the sensitivity of the perovskite thin film to solvent, preparation of metal top electrode by solution process is of great challenging. This is the key technology for the realization of fully solution processed perovskite solar cells. In this paper, we report the preparation of transparent silver nanowires (AgNW) top electrode for perovskite solar cells using inkjet printing process. Experiment results demonstrate that low device performance with low fill factor was obtained when the AgNW is directly printed onto the PC61 BM layer. This is ascribed to the mismatched work functions of the AgNW electrode and PC61 BM layer, and the solvent assisted chemical corrosion of the AgNW electrode by halogen anions. By inserting a thin layer of polyethylenimine (PEI), the charge injection barrier between PC61 BM and AgNW electrode was minimized. More importantly, such a thin PEI layer suppresses the chemical corrosion of AgNW electrode during printing, yielding a condensed and uniform AgNW networks. The introduction of a thin PEI layer greatly improves the device performance and stability. A high power conversion efficiency of 14.17% with an averaged light transmittance of 21.2% was achieved for the PEI/AgNW cells. In addition, improved performance stability was measured for the PEI/AgNW cells. Abstract : Fully solution‐processed semi‐transparent perovskite solar cells with a highest PCE of 14.17% are realized by incorporating a thin lay of polyethylenimine (PEI), which acts as the interfacial work function modification layer as well as the protection layer of the printed AgNW electrode by suppressing the chemical corrosion of AgNW electrode during printing.